Risikofaktoren für einen schweren COVID-19-Verlauf in einer Hotspot-Region der ersten und zweiten SARS-CoV-2-Infektionswelle in Deutschland - Richter, Steffi; Finkenzeller, Thomas; Uter, Wolfgang; Drexler, Hans; Wolfschmidt, Anna (Gesundheitswesen, 2024)
Background During the first wave of the SARS-CoV-2 pandemic, Weiden Hospital was a hotspot and was thus in an exceptional medical situation. This study deals with the question of whether the recognized risk factors for a severe course of COVID- 19 also apply to the patients treated in Weiden Hospital during this time or whether other factors could have influenced patient outcomes. Methods In a retrospective analysis, data on 669 patients of Weiden Hospital with proven SARS-CoV-2 infections in the first year of the pandemic were evaluated. Risk factors for a severe case of COVID-19 were determined from medical and demographic information in a univariate analysis and subjected to logistic regression. The logistic regression analysis was performed for the overall collective as well as separately for patients from Wave 1 (3-6/2020) and 2 (7-12/2020). Results Looking at all of 2020, significant risk factors for severe COVID-19 included being male, being a smoker, being 71 years or older, and a history of depression. All other commonly recognized risk factors were not applicable for the Weiden collective. When looking at both waves separately, in Wave 1 age was not a significant risk factor, whereas in Wave 2 an age of 61 years or older was associated with an increased risk of severe progression. For patients who were admitted to hospital in Wave 2, the risk of severe progression was reduced almost by half. Conclusion It can be assumed that patient outcomes in Weiden's hotspot collective were predominantly determined by non-individual factors, like the difficult care situation in a hotspot clinic at the beginning of the pandemic. In preparation for future pandemics, provision of sufficient resources might significantly contribute to better patient outcomes.
CRIS-Team Scopus Importer:2024-11-29
Keywords: COVID-19; erste Welle; Hotspot; Pandemie; schwerer Verlauf